Role of academic library in creating students’ mental health literacy - Neneng Komariah; Encang Saepudin; Rizki Nurislaminingsih (Record and Library Journal, 2022)
Background of the study: Mental health literacy is a very important skill because mental health is as important as physical health. University students must have mental health literacy because they face heavy pressure in the learning process and in social interactions. Academic libraries can play an active role in creating students' mental health literacy.Purpose: to identify and explain how the role of academic libraries in creating students' mental health literacy. Method:  It is a literature review, namely reviewing the books, journal articles, news, reports on mental health, mental health among students, the function and role of the academic library. Next, synergize the results of the study with the results of the researchers' thoughts. Findings:  Academic libraries can carry out various activities as an effort to create students’ mental health literacy, namely providing easy access to mental health information sources through library  collections development and providing mental health corners; promoting mental health collections in the library; organize mental health literacy campaigns through events such as seminars; providing health consultation facilities in collaboration with mental health professionals such as psychologists and psychiatrists. Conclusions: Academic libraries can play an active role in creating students' mental health literacy by utilizing their resources and by collaborating with professionals.